Antihyperlipidemic and Antioxidative Potentials of Onion (Allium cepa L.) Extract Fermented with a Novel Lactobacillus casei HD-010 - Yang, Woong-Suk; Kim, Jin-Chul; Lee, Jae Yong; Kim, Cheorl-Ho; Hwang, Cher-Won (HINDAWI LTD, 2019)
The purpose of this study was to investigate antihyperlipidemic and antioxidative potentials of onion (Allium cepa L.) extract fermented with a novel Lactobacillus casei HD-010. In general, fermented onion extract is used for its antioxidative activity (ORAC), inhibitory effect on adipocytes differentiation, quercetin contents, and antihyperlipidemic activities. However, the effect of fermented onion extract on hyperlipidemia after oral administration using ApoE-deficient mice has not been reported yet. To understand the effect of fermented onion extract on hyperlipidemia, we used benzafibrate (10 mg/kg, bw/day) as a positive control in the present study. Serum was collected every week to analyze levels of low density lipoprotein (LDL), high density lipoprotein (HDL), triglyceride (TG), and cholesterol, 3-hydroxy-3-methylgutaryi-CoA (HMG-CoA) reductase activity, and cholesterol ester transport protein (CETP) activity. In the fermented onion-treated group, HDL level was significantly increased while levels of TG and LDL were significantly decreased compared to those in the control group. In addition, the inhibition activity of HMG-CoA reductase was increased 20% in the fermented onion-treated group at 100 mg/kg. CETP activity has been observed to be significantly inhibited in the fermented onion-treated groups compared to that in the control group. These results suggest that fermented onion has a preventive/therapeutic effect on hyperlipidemic disease. It might have potential to be developed as a functional food.
Keywords: DIET; CHOLESTEROL; BIOREACTORS; METABOLISM; RAW; MEN